Pengaruh Konflik Kerja dan Stres Kerja terhadap Kinerja Karyawan - Samsudin, Acep; Prabowo, Budi; Asfadela, Devi Meisa Putri; Selvina, Putry Meysa; Makatita, Tegar Fajar Ramadhan; Fitri, Amelia Cahya Syah (As-Syirkah: Islamic Economic & Financial Journal, 2024)
There is no way to completely escape work-related issues like conflict and stress. workers' performance is negatively impacted by work conflict and stress. This indicates that when workers encounter high levels of stress and job conflict, their performance will fall dramatically. Finding out how stress and conflict at work affect productivity is the driving force behind this study. The research in this study is descriptive in nature and employs qualitative approaches. Findings from studies This demonstrates that stress at work has a negative and statistically significant effect on employee performance, whereas conflict at work has a positive and statistically significant effect on employee performance.